NUTRITIONAL EVALUATION OF DIETS OF LOW-INCOME RURAL POPULATION FROM NWFP, PAKISTAN - Jan, M; Mahmood, F; Zeb, A; Chaudry, M A (Biological Sciences - PJSIR, 2003)
Results are presented for the levels of protein, fat, fiber, ash, iron, iodine, CHO and total energy in different food groups and whole diets collected from ten families. The data revealed that protein content was higher in meat group (14.6%) followed by cereal (5.8%), leafy vegetable (2.1%), root vegetable (1.7%) and lowest in salad (0.7%) groups. Maximum fiber (0.8%) and ash (2.8%) were found in leafy vegetable and meat groups respec- tively. The average nutrient contents consumed by members of 10 families revealed that the dinner time diets contain more nutrients than the breakfast and lunch time diets. The results indicated that except for carbohy- drate contents, nutrients were present in comparatively larger quantities in the diets of higher income group than the other group. Fat contents were on adequate levels in both the groups (above 80% of RDA).